Does bimanual coordination training benefit inhibitory function in older adults? - Torre, Marta Maria; Langeard, Antoine; Alliou, Louis; Temprado, Jean-Jacques (Frontiers in Aging Neuroscience, 2023)
Introduction Whether complex movement training benefits inhibitory functions and transfers the effects to non-practiced motor and cognitive tasks is still unknown. The present experiment addressed this issue using a bimanual coordination paradigm. The main hypothesis was that bimanual coordination training allows for improving the involved cognitive (i.e., inhibition) mechanisms and then, transferring to non-practiced cognitive and motor tasks, that share common processes. Methods 17 older participants (72.1 ± 4.0 years) underwent 2 training and 3 test sessions (pre, post, and retention one week after) over three weeks. Training included maintaining bimanual coordination anti-phase pattern (AP) at high frequency while inhibiting the in-phase pattern (IP). During the test sessions, participants performed two bimanual coordination tasks and two cognitive tasks involving inhibition mechanisms. Transfer benefits of training on reaction time (RT), and total switching time (TST) were measured. In the cognitive tasks (i.e., the Colour Word Stroop Task (CWST) and the Motor and Perceptual Inhibition Test (MAPIT)), transfer effects were measured on response times and error rates. Repeated one-way measures ANOVAs and mediation analyses were conducted. Results Results confirmed that training was effective on the trained task and delayed the spontaneous transition frequency. Moreover, it transferred the benefits to untrained bimanual coordination and cognitive tasks that also involve inhibition functions. Mediation analyses confirmed that the improvement of inhibitory functions mediated the transfer of training in both the motor and cognitive tasks. Discussion This study confirmed that bimanual coordination practice can transfer training benefits to non-practiced cognitive and motor tasks since presumably they all share the same cognitive processes.